Perilaku Masyarakat Parit Keladi 1 dalam Usaha Pertolongan Pertama pada Kecelakaan Kerja - Sutrisno, Sutrisno; Ronas, Mahin Ridlo; Safira, Annisa; Almumtahanah, Almumtahanah (Society : Jurnal Pengabdian Masyarakat, 2024)
Workplace accidents are a serious issue in the professional world, including in the agricultural sector, which serves as the primary livelihood for many communities. This research aims to understand community behavior in providing first aid for workplace accidents. Using a qualitative method with an ethnographic approach, this study involved observation, structured interviews, and documentation of four research subjects. The results indicate that the community still relies heavily on traditional treatment methods, such as the use of leaves (Kalanchoe pinnata, Melastoma malabathricum) and banana stem sap to treat wounds. However, there is an awareness of the importance of combining traditional practices with modern medical approaches. In conclusion, although traditional practices remain dominant, there is a need to enhance community skills and knowledge about modern first aid, as well as to integrate traditional practices with modern medical care to improve the effectiveness of handling workplace accidents in the village.